Brilink User Satisfaction Analysis in Kupang City - Redentus Natalis Jelahut; Nikson Tameno; Maria I. H. Tiwu (Formosa Journal of Sustainable Research, 2023)
This research entitled analysis of BRILink user satisfaction in Kupang City (case study of Nusa Cendana University Students) is based on the government's efforts to facilitate access to financial services throughout Indonesia and increase public financial access, namely with a branchless banking program in which efforts to create innovation and expansion financial inclusion called BRILink. This research aims to explain the influence of service quality and transaction experience on user satisfaction, namely Nusa Cendana University students, as well as the benefits obtained for both the author, Bank BRI, and subsequent researchers. The research uses quantitative methods using analysis tests to determine the influence of quality and transaction experience. or not regarding the suitability of BRILink users. Based on the research conducted, it has been found that there is only one variable out of the two dependent variables that influences the independent variable, namely the transaction experience variable which influences the user satisfaction variable